Medium-term results after treatment of percutaneous tennis elbow release under local anaesthesia - Yigit, Şeyhmus (Acta Biomedica Atenei Parmensis, 2020)
Background: The purpose of this study was to evaluate  the results of the technique of percutaneous release of common extensor procedure under local anesthesia for lateral epicondylitis and to emphasize its simplicity. Methods: Forty seven elbows (41 patients) were treated surgically for lateral epicondylitis in the outpatient minor procedure room under local anaesthesia. The indication for surgery was continuation of sypmtoms (such as pain, movement and power loss) despite conservative treatment lasting more than six months The treatment results were assessed using the visual analogue scale (VAS) and Mayo Elbow Performance Score (MEPS). Results: Twentysix  right elbows and fifteen left elbows were treated surgically. Dominate elbow rate was 74%. The follow-up period was 36 to 72 months (mean 52 months). All patients had full range of motion. The average post operative pain score was 2.6(range 0 to 9).The average post operative MEPS score was 82 (range 40 to 100). ). Sixteen patients had excellent, twenty  patients had good, two patients had fair and three patients had poor outcomes (repetitive problems). Conclusion: The percutaneous release of the common extensor origin is an important treatment option with minimal morbidity, safety, simplicity and good to excellent results in most patients. The procedure can be performed under local anaesthetic and leave a rarely visible scar.